Pirfenidone regulates seizures through the HMGB1/TLR4 axis to improve cognitive functions and modulate oxidative stress and neurotransmitters in PTZ-induced kindling in mice - Dahalia, Mansi; Gupta, Sparsh; Majid, Haya; Vohora, Divya; Nidhi, (Frontiers in Pharmacology, 2025)
BackgroundEpilepsy is a neurological disorder characterized by recurrent seizures due to abnormal electrical activity in the brain. Pirfenidone, an antifibrotic drug, has shown anti-inflammatory and antioxidant properties in various disease models, including neurological conditions. However, its potential anticonvulsant effects have not been thoroughly explored. This study aims to evaluate the anticonvulsant potential of pirfenidone in a pentylenetetrazol-induced kindling model of epilepsy, focusing on its effect on seizure activity, cognition, antioxidant profiles, inflammatory markers, neurotransmitter balance, liver enzyme levels, and histopathological changes.MethodsHealthy male Swiss albino mice were subjected to an acute Increasing Current Electroshock test and chronic pentylenetetrazol-kindling model. Pirfenidone was administered at doses of 100, 200, and 300 mg/kg, orally, with sodium valproate as a standard drug. Seizure severity and cognitive function were assessed in the pentylenetetrazol-kindling model, along with biochemical assays that evaluated antioxidant enzymes, inflammatory markers, neurotransmitter levels, and liver enzyme levels. Histopathological changes were also assessed in the hippocampus and cortex of experimental mice.ResultsPirfenidone at 200 mg/kg and 300 mg/kg significantly increased Seizure Threshold Current in the Increasing Current Electroshock test, indicating a protective effect against seizures. In the pentylenetetrazol-kindling model, pirfenidone delayed seizure onset and reduced severity, with the 300 mg/kg dose showing the strongest impact. Pirfenidone also demonstrated significant improvements in cognitive function, as evidenced by enhanced performance in passive avoidance and elevated plus maze tests. Antioxidant profiles showed increased levels of superoxide dismutase, catalase, and reduced glutathione, with a corresponding reduction in malondialdehyde and acetylcholinesterase levels. Pirfenidone significantly reduced pro-inflammatory cytokines including interleukin-6, interleukin-1β, transforming growth factor-β, tumor necrosis factor- α, high-mobility group box-1, and toll-like receptor-4, elevated gamma-aminobutyric acid, decreased glutamate levels, modulated aspartate aminotransferase and alanine aminotransferase levels. Histopathological analysis revealed that pirfenidone ameliorated cellular disintegration and neuronal damage in the hippocampus and cortex.ConclusionPirfenidone shows potential as an anticonvulsant, anti-inflammatory, hepatoprotective, and neuroprotective agent, with additional benefits in improving cognition and oxidative stress profiles in epilepsy treatment. Further studies are required to explore its long-term safety and efficacy.